Wspólnota komunikatywna jako narzędzie opisu w historii języka polskiego - nowe perspektywy = Communicative community in the history of the Polish language - new perspectives - Woźniak, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the history of the Polish language, the concept of a communicative community was used to understand a community connected by bonds of origin and territory, and therefore de facto a national (ethnic) community. In this sense, this term was popularized in Polish linguistics by Stanisław Borawski. The article proposes the introduction of two concepts to the historical-linguistic description: the Polish state community and the Polish linguistic community, which refers to the distinction defined by Ludwik Zabrocki into the communicative community and the linguistic community.
Keywords: historia języka polskiego; wspólnota komunikatywna; wspólnota językowa; wielojęzyczność; history of the Polish language; communicative community; linguistic community; multilingualism